(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is to know (the effect of the hesitating cards strategy in the collection of a subject. The rules of the Arabic language for students of the fourth scientific grade) The experimental approach was adopted as a method. For this research, the experimental design with the experimental and control groups was chosen as a design for his research. The research community consisted of fourth-grade students in the Diyala Education Directorate and from there, It randomly chose Dirar Ibn Al-Azwar Preparatory School for Boys as a sample for this research. The researcher prepared an achievement test consisting of (50) items as a tool for his research. The honesty and reliability and the used appropriate statistical methods in processing his data was assured . The application of the test reached that there is a statistically significant difference at the level of significance (0.05) between the average scores of the students of the two research groups in the achievement test. In the interest of the experimental group, and in light of this, the researcher drew several conclusions. He made several recommendations and suggested several suggestions.